2018
DOI: 10.1016/j.canlet.2017.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Favorable biodistribution, specific targeting and conditional endosomal escape of RNA nanoparticles in cancer therapy

Abstract: The past decades have witnessed the successful transition of several nanotechnology platforms into the clinical trials. However, specific delivery of therapeutics to tumors is hindered by several barriers including cancer recognition and tissue penetration, particle heterogeneity and aggregation, and unfavorable pharmacokinetic profiles such as fast clearance and organ accumulation. With the advent of RNA nanotechnology, a series of RNA nanoparticles have been successfully constructed to overcome many of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 137 publications
0
60
0
Order By: Relevance
“…Different strategies have been developed to ensure endosomal release, one mechanism proposed was the "proton sponge," which are typically polyamines that work by absorbing free protons in the endosomes. Protonable molecules induce an inflow of ions and water into the endosome, subsequently rupturing the endosome and releasing endosome contents into the cell [60]. Another mechanism utilizes an approach modelled on how enveloped viruses induce endosomal escape by fusion of the viral envelope with the endosome membrane, allowing the viral capsid to enter the cytoplasm.…”
Section: Endosomal Escapementioning
confidence: 99%
“…Different strategies have been developed to ensure endosomal release, one mechanism proposed was the "proton sponge," which are typically polyamines that work by absorbing free protons in the endosomes. Protonable molecules induce an inflow of ions and water into the endosome, subsequently rupturing the endosome and releasing endosome contents into the cell [60]. Another mechanism utilizes an approach modelled on how enveloped viruses induce endosomal escape by fusion of the viral envelope with the endosome membrane, allowing the viral capsid to enter the cytoplasm.…”
Section: Endosomal Escapementioning
confidence: 99%
“…RNA‐based materials were fabricated based on both the Watson–Crick and the noncanonical base pairing (such as guanine with adenine or uracil) . Due to their flexible structure, numerous loops and motifs, and a higher thermal stability than DNA‐based materials, RNA‐based materials showed enormous potential as alternative gene therapeutic agents …”
Section: Gene Therapymentioning
confidence: 99%
“…To date, many important barriers (e.g., chemical stability and thermodynamic stability) in the field of RNA nanotechnology have been successfully overcome (Corey, ; Khisamutdinov, Jasinski, & Guo, ; Shu et al, ). The progress in these aspects has been discussed in previous reviews (Jasinski et al, ; Li et al, ; Xu et al, ). Recently, however, more studies have been reported on understanding the broad mechanisms that define the pharmacological and immunological profile of RNA nanoparticles.…”
Section: Introductionmentioning
confidence: 99%